1995
DOI: 10.1212/wnl.45.7.1333
|View full text |Cite
|
Sign up to set email alerts
|

No association of the 11778 rnitochondrial DNA mutation and multiple sclerosis in Japan

Abstract: Leber's hereditary optic neuropathy (LHON), a maternally inherited disease causing severe bilateral visual loss in young men, is linked to 12 point mutations in mitochondrial DNA, the most common of which is at the nucleotide position 11778. The 11778 point mutation has also been detected in several patients with possible multiple sclerosis (MS), especially women with severe visual loss in both eyes. Because frequent and severe optic neuropathy is a feature of MS in Japan, we screened 80 Japanese MS patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…30 Several studies in patients with MS have failed to demonstrate the primary LHON mutations among these. [31][32][33] In conclusion, it would seem that LHON patients have increased risk of an MS-like disease, but that primary LHON mutations do not play a role in the majority of cases of MS.…”
Section: Discussionmentioning
confidence: 88%
“…30 Several studies in patients with MS have failed to demonstrate the primary LHON mutations among these. [31][32][33] In conclusion, it would seem that LHON patients have increased risk of an MS-like disease, but that primary LHON mutations do not play a role in the majority of cases of MS.…”
Section: Discussionmentioning
confidence: 88%
“…All three primary LHON mutations have been found to be associated with MS or MS-like syndromes in the European and North American population [2, 3, 4, 5, 6, 7, 8]. However, the only study in Asians reported no association between Japanese MS patients and nt 11778 mtDNA mutations [10]. Except for this single study which tested only for the presence of the nt 11778 mtDNA mutation [10], little information is available on the association of LHON mutation with MS in Asians.…”
Section: Introductionmentioning
confidence: 99%
“…However, the only study in Asians reported no association between Japanese MS patients and nt 11778 mtDNA mutations [10]. Except for this single study which tested only for the presence of the nt 11778 mtDNA mutation [10], little information is available on the association of LHON mutation with MS in Asians. The purpose of the present study was to check for the existence of LHON mtDNA mutations in Korean MS patients suffering from optic neuropathy (ON).…”
Section: Introductionmentioning
confidence: 99%
“…Hanefeld et al [16]reported that none of 36 children and 30 adults with MS harbored the nt-3460 or nt-11778 mutations, while Nishimura et al [17]noted that of 80 Japanese MS patients screened, none had the nt-11778 mtDNA mutation. Mayr-Wohlfart et al [18]did not find any of the three primary LHON mtDNA mutations in 100 MS patients with ON.…”
Section: Discussionmentioning
confidence: 99%